Eagle syndrome: A review of current diagnostic criteria and evaluation strategies - Vishlesh Arora; Arvind Shetti; Vaishali Keluskar (Wolters Kluwer Medknow Publications, 2008)
The mineralized and elongated styloid process and Eagle's syndrome are similar processes of elongation in which mineralization of the stylohyoid ligament leads to styloid process of the temporal bone. The mineralized and elongated styloid process and Eagle's syndrome differ significantly in terms of the symptoms displayed and the treatment modalities that are sought. The mineralized and elongated styloid process refers to unilateral or bilateral elongation of the styloid process that does not result in any significant pain, discomfort, or limitation of neck movement. It often remains asymptomatic until it is discovered on extraoral radiographs. Eagle's syndrome refers to pain and discomfort in the cervicofacial region resulting specifically from the elongated styloid process. Surgical shortening may be the only treatment that will alleviate the patient's symptoms.This article reviews the entire process of elongation pertaining to the styloid process and discusses the associated syndromes, including current knowledge of the theories of elongation, diagnostic criteria and treatment strategies.